Asymptomatic gallstones: Cumulative incidence proportion, incidence rate, and risk factors for symptoms development: Systematic review and meta-analysis - Mohammad Alzoubi; Ahmad Omar Saleh; Farah Al Omari; Kinda Shatnawi; Batool Hyari; Ala’a Qashou; Khaled Daradka; Salam Daradkeh; Mohammad Abu Hilal; Alessandro Parente (PLoS ONE, 2026)
Objectives This review aims to evaluate the cumulative incidence proportion, incidence rate, and risk factors for progression of incidentally diagnosed, asymptomatic gallstones to symptomatic gallstone disease (GSD) and associated complications. Design Systematic Review and Meta-Analysis. Data source Four electronic databases were searched (PubMed, Scopus, Web of Science, and ScienceDirect) with no start date restriction, up to July 2025. Eligibility criteria Inclusion criteria: patients who were diagnosed with gallstones incidentally. Exclusion criteria: known history of GSD, patients who have undergone bariatric surgery or cholecystectomy, recurrence of gallstones, pregnancy, estrogen therapy, pediatric age group, review, case report, case series, editorial, letters, and abstracts. Data extraction and synthesis This review is registered with PROSPERO (CRD42024526889). Primary screening by title and abstract was conducted in Rayyan; full-text screening was performed, and the references of the included studies were manually searched for relevant papers. Data were extracted into an Excel sheet, and the meta-analysis was conducted using RStudio. Single-arm outcomes were summarized in proportion, and comparative outcomes were summarized in Risk Ratio (RR) for categorical outcomes and mean difference for continuous ones. Heterogeneity was evaluated using the I statistic and the Q test. Results Eight cohort studies, reported in 9, with a total of 25,924 participants, were included. The cumulative incidence proportion of symptomatic progression was 0.10, 95% CI: [[0.10; 0.11]] at 5 years, 0.19, 95% CI: [0.14; 0.25] at 10 years, and 0.26, 95% CI: [0.12; 0.40] at 15 years. Alcohol consumption (RR: 1.32, 95% CI: [1.27; 1.38]) and hyperlipidemia (RR: 1.19, 95% CI: [1.07; 1.32]) were identified as risk factors. Chronic liver disease (RR: 0.76, 95% CI: 0.67; 0.87) and male gender (RR: 0.54, 95% CI: 0.33; 0.87) were observed as protective factors. Conclusion This systematic review examines factors influencing symptomatic progression of ASG and guides the identification of high-risk patients who may benefit from prophylactic measures such as cholecystectomy.